Correlations of Corneal Spherical Aberration with Astigmatism and Axial Length in Cataract Patients - Min Zhang; Dongjin Qian; Qinghe Jing; Jiahui Chen; Michael Deng; Yongxiang Jiang (Journal of Ophthalmology)
Purpose. To clarify the distribution of corneal spherical aberrations (SAs) in cataract patients with different corneal astigmatism and axial length. Setting. Department of Ophthalmology and Vision Science of the Eye and ENT Hospital of Fudan University, Shanghai, China. Design. Retrospective case series. Methods. The axial length, corneal SAs, and other corneal biometrics were collected in cataract patients with Pentacam HR and IOLMaster 500. The statistical analysis of the corneal SAs was based on the stratification of axial length and anterior corneal astigmatism. Results. In total, 6747 eyes of 6747 patients were recruited, with 2416 eyes (58.17 ± 16.81 years old) in the astigmatism group (anterior corneal astigmatism ≥1 D) and others (61.82 ± 12.64 years old) in the control group. In patients with astigmatism <2 D, the total and anterior SAs decreased as the axial length increased (P<0.001). The total corneal SAs of patients with astigmatism of 2-3 D stabilized at around 0.29 μm, whereas those of patients with anterior corneal astigmatism ≥3 D tended to be variable. Age and anterior corneal astigmatism had positive and negative effects, respectively, on SA in the regression model. Conclusions. Axial length has a negative effect on the anterior and total corneal SAs, which stabled around 0.33 μm and 0.30 μm in patients with axial length of ≥26 mm, respectively. Individualized SA adjustments are essential for patients undergoing aspheric toric IOL implantation with preoperative anterior corneal astigmatism of 1-2 D or ≥3 D. Toric IOLs with a negative SA of −0.20 μm are recommended for patients with anterior corneal astigmatism of 2-3 D if no customized therapy is warranted.